Asymmetries and Rigidities in Wage Adjustments by Firms - Holzer, Harry J.; Montgomery, Edward B. (The Review of Economics and Statistics, 1993)
In this paper we use micro data from the Employment Opportunity Pilot Project (EOPP) surveys of firms in 1980 and 1982 to test for labor market rigidities and asymmetries in response to demand shifts.We analyze wage and employment adjustments to positive and negative shifts, as measured by sales growth between 1979 and 1981.The analysis is done for both entire sample of firms and for selected subsamples based on firm size, unionization, industry and skill mix.The results show that wage adjustments appear to be fairly rigid, compared with employment adjustments.They also appear to be quite asymmetric, with significant adjustments in response to positive shifts but little adjustment in response to negative shifts.These asymmetries are not more pronounced in large firms, manufacturing, heavily-waged or highly-skilled industries than in other firms or industries.pattern of asymmetry.